Vacuum-ultraviolet absorption cross-sections of functionalized four-carbon species. (December 2022) - Doner, Anna C.; Webb, Annabelle R.; Dewey, Nicholas S.; Hartness, Samuel W.; Christianson, Matthew G.; Koritzke, Alanna L.; Larsson, Alexander; Frandsen, Kelsey M.; Rotavera, Brandon
Highlights: Quantitative, high-resolution absorption spectra measured in the vacuum-ultraviolet for four-carbon species, including hydrocarbons and oxygenates, the majority of which for the first time. Absorption cross-sections measured for intermediates relevant to combustion chemistry and atmospheric chemistry. Detailed uncertainty analysis calculations conducted. Extensive comparison with literature. Abstract: Absorption cross-sections were measured in the vacuum ultraviolet from 5.17 – 9.92 eV using differential absorption spectroscopy for 33 four-carbon species: n -butane, trans -2-butene, cis -2-butene, butanal, butyric acid, ethyloxirane, trans- 2, 3-dimethyloxirane, cis -2, 3-dimethyloxirane, 2-methyloxetane, 2, 2′-bioxirane, vinyl oxirane, 3, 4-epoxybutan-2-one, diacetyl, diethyl ether, ethyl vinyl ether, vinyl acetate, acetic anhydride, 1-butanol, 3-buten-1-ol, 1‑hydroxy-butan-2-one, 1‑hydroxy-butan-3-one, 2, 3-epoxybutan-1-ol, 3, 4-epoxybutan-1-ol, 2-oxetanemethanol, butanone, methyl vinyl ketone, 4 H -1, 3-dioxine, allyl formate, 2-oxobutanal, 4-hydroxybutanal, 2-methyloxetan-3-one, cis ‑but-2-en-1-ol, and trans -2‑but-enal. Uncertainties were quantified in all cases by accounting for errors in gas-phase concentration, experimental repeatability, and signal-to-noise ratio as a function of photon energy. With the exception of 2-oxobutanal, which is reported with an uncertainty of 10%, convolving the sources of error using the root-sum-square method led to an upper limit of 5% uncertainty above the detection limit, which is largely attributable to chemical purity. The primary objective of the present work is to provide absolute cross-sections along with quantified uncertainty limits. The majority of the absorption spectra, which reflect electronic transitions such as σ → σ * and n → σ *, are reported for the first time and provide insight into fundamental chemical physics, such as vibrational band structure and Rydberg transitions. The quantitative spectra in the present work facilitates the discovery of chemical intermediates that support improvement in the accuracy of computational models for low-temperature combustion and atmospheric chemistry.